Pharmaconutrition administration on outcomes of elective oncological surgery for gastrointestinal malignancies: is timing everything?—a review of published meta-analyses until the end of 2016 - Osland, Emma; Memon, Breda; Memon, Muhammed Ashraf (Translational Gastroenterology and Hepatology; Vol 3 (August 2018): Translational Gastroenterology and Hepatology, 2018)
The last 25 years have seen an increasing number of publications attesting the benefits of pharmaconutrition in the management of patients undergoing elective oncological gastrointestinal surgery. A number of randomized controlled trials and meta-analyses suggest the use of pharmaconutrition in this group of patients produces superior outcomes to standard nutritional formulations in terms of postoperative infective complications, anastomotic breakdown and length of hospital stay. The use of pharmaconutrition products, therefore, has gained increasing acceptance for use in elective gastrointestinal oncological surgical populations and been incorporated into practice guidelines. However, there remains doubts as to the robustness of such data supporting these recommendation. This is because studies reporting improved outcomes with pharmaconutrition (I) frequently compare this intervention with non-equivalent control groups; (II) do not report on the actual nutritional provision received by study participants; (III) overlook the potential impact of industry funding on research conducted and (IV) do not adopt a multi-disciplinary approach to the research undertaken. For these reasons, a critical re-appraisal of the use and recommendations of pharmaconutrition in this group of patients is urgently warranted to resolve some of the above mentioned issues. The aim of this review was to analyse meta-analyses published until the end of 2016 in this area to highlight the strengths and weakness of the present research and prioritize certain areas which will benefit from future research.